Features of Psychological Ready of the Future Assistant Dentist in the System Didactic Interaction - Viznyuk , Inessa; Dolinny, Sergey (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article shows the essence of psychological training of an assistant dentist, as well as his competence characteristics and features of the professional direction, through experimental research, implemented the training of such a specialist in a number of well-known medical institutions of Ukraine. The aim of the research is the theoretical substantiation and experimental diagnostics of the peculiarities of the psychological readiness of the future assistant dentist in the system of didactic interaction of ZVO. The methods used include: Berlin Questionnaire (BQ), which assesses their medical abilities based on their assessment results, the method "Motivation to choose a medical profession" AP Vasilkova, test-questionnaire "Production situations", the author’s method of three-subject questionnaire A. N. Humenuk. The conclusions present and practically prove the effectiveness of didactic conditions that provide psychological training of the assistant dentist in medical schools. It is indicated that the system of didactic interaction of the educational institution is focused on the pedagogical support of the relevant actualization of the student as a subject of his own professional choice. The effectiveness of the organizational and pedagogical conditions of the psychological readiness of the future assistant dentist in the system of didactic interaction developed and implemented in the educational process of the educational institution is presented. Author’s variants were used: interactive three-subject planning and adaptive management in the organization of educational process of students; methods of work in individual and collective forms on the ways of forming the subjective experience of the future specialist. The efficiency of introduction of organizational and pedagogical conditions of professional training of the assistant dentist is practically proved. During the experimental study, respondents eventually rethought the "object" of their activities and crossed the previously opaque boundaries between medical care and traditional training of students in the conditions of free economic zone.